Specific dyspeptic symptoms are associated with poor response to therapy in patients with gastroesophageal reflux disease. Issue 1 (February 2017) - D'Alessandro, A; Zito, FP; Pesce, M; Andreozzi, P; Efficie, E; Cargiolli, M; Maione, F; De Palma, GD; Cuomo, R; Sarnelli, G
Introduction: In patients with gastroesophageal reflux disease (GORD), co-existence of functional dyspepsia (FD) is known to be associated with poor response to proton pump inhibitors (PPIs), but the contribution of specific dyspepsia symptoms has not yet been systematically investigated. Objective: We aimed to characterize the impact of dyspepsia symptoms on response to PPIs in patients with GORD. Methods: The enrolled subjects were consecutive patients with a diagnosis of GORD. All patients underwent a 24 hour pH–impedance test, while on PPI therapy. Patients were divided into two groups, refractory and responders, according to the persistence of GORD symptoms. A standardized questionnaire for FD was also administered to assess presence of dyspepsia symptoms. Results: In the subgroup of refractory patients FD was more prevalent than in responders, with post-prandial fullness, nausea, vomiting, early satiation and epigastric pain being significantly prevalent in refractory GORD patients. In the multivariate analysis only early satiation and vomiting were significantly associated with poor response to PPIs. Conclusion: Co-existence of FD is associated with refractory GORD. We showed that only early satiation and vomiting are risk factors for poor response to therapy with PPIs. Our findings suggest that symptoms of early satiation and vomiting would help to identify the subset of PPI-refractory GORD patients.